Writing Better Research Articles for Publication - Budhathoki, Mahendra Kumar (Cognition, 2023)
Background: Many research articles have been rejected by journals although authors provide the original subjects or ideas. Scholars and experts comment that the research papers are not well-written, but they do not provide the concrete guidelines for writing good research papers. Objective: This article aims to provide generic structure, practical guidelines and advice for writing each section of a research paper. Methods: The study used descriptive qualitative method and observation and notetaking tools to collect the data/information. Key terms/phrases like ‘how to write research articles’, ‘structuring research papers’ were used to collect the materials. The author observed the structure of research articles and synthesized some review articles about writing each section of a research paper; then the generic guidelines and practical advice were prepared for writing a research article. Findings: The IMRaD structure (introduction, methods, result and discussion) in a research paper has high impact. The introduction briefly informs what the research was done why and how. Method section explains in detail what method was utilized why and how. Results presents what the data found without explanation. Discussion section carries the meanings of the results concerning with present contexts and previous research. Conclusion and limitation sections are prepared with the supports of the results. For other sections of an article, the author guidelines should be followed. Conclusion: Author guidelines, generic structure of a research article, practical guidelines and advice prevent the most common errors and help the author produce a good research article for publishing. This article gives teachers, students, authors, editors, peer-reviewers and readers a helping hand in writing/reading a research paper.